IDENTIFIKASI TUMBUHAN BAWAH PADA TEGALAN DENGAN TIGA M ACAM TANAMAN POKOK DI DESA PRIGELAN, PITURUH, PURWOREJO - , NINDHA MEGA LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Undergrowth is a plant that is under a layer of trees or plants that can be classified in the bushes, herbs, as well as the types of mosses that live on the surface of the ground as ground cover. Different types of land, in this case is the moor, is thought to cause the emergence of plant under species different. This research aimed to determine the variation of plant under species the moor which have different staple crops. Research conducted in the village prigelan, pituruh districts, counties purworejo. Sampling is done by making random plots the number nine plots in each type of staple crops. Plots were made by 27 pieces with a size of 2m x 2. Based on the results of research conducted in the area of the moor with three kinds of staple crops are bananas, melinjo, and sengon found as many as 45 species of plants are detailed below as follows: 18 types of staple crops on dry land with sengon, 18 kinds of the principal crops cultivated with bananas, and 17 types of staple crops on dry land with melinjo. The family Asteraceae and Poaceae dominate is. The kind that has the highest IVI in upland banana is Isachne globosa with a value of 18.52%, while on the moor melinjo is Rubus niveus with value 18.35%, and the moor is Euphorbia hirta sengon with a value of 17.50%.